In Severe Alcoholic Hepatitis, Serum Keratin-18 Fragments Are Diagnostic, Prognostic, and Theragnostic Biomarkers. (2nd November 2020) - Atkinson, Stephen R.; Grove, Jane I.; Liebig, Stephanie; Astbury, Stuart; Vergis, Nikhil; Goldin, Robert; Quaglia, Alberto; Bantel, Heike; Guha, Indra Neil; Thursz, Mark R.; Newcombe, Paul; Strnad, Pavel; et al.
Abstract : INTRODUCTION: Up to 40% of patients with severe alcoholic hepatitis (AH) die within 6 months of presentation, making prompt diagnosis and appropriate treatment essential. We determined the associations between serum keratin-18 (K18) and histological features, prognosis, and differential response to prednisolone in patients with severe AH. METHODS: Total (K18-M65) and caspase-cleaved K18 (K18-M30) were quantified in pretreatment sera from 824 patients enrolled in the Steroids or Pentoxifylline for Alcoholic Hepatitis trial (87 with suitable histological samples) and disease controls. RESULTS: K18 fragments were markedly elevated in severe AH and strongly predicted steatohepatitis (alcoholic steatohepatitis) on biopsy (area under receiver operating characteristics: 0.787 and 0.807). Application of published thresholds to predict alcoholic steatohepatitis would have rendered biopsy unnecessary in 84% of all AH cases. K18-M30 and M65 were associated with 90-day mortality, independent of age and Model for End-stage Liver Disease score in untreated patients. The association for K18-M65 was independent of both age and Model for End-stage Liver Disease in prednisolone-treated patients. Modelling of the effect of prednisolone on 90-day mortality as a function of pretreatment serum K18 levels indicated benefit in those with high serum levels of K18-M30. At low pretreatment serum K18 levels, prednisolone was potentially harmful. A threshold of K18-M30 5 kIU/L predicted therapeutic benefit from prednisolone above this level (odds ratio: 0.433, 95% confidence interval: 0.19–0.95, P = 0.0398), but not below (odds ratio: 1.271, 95% confidence interval: 0.88–1.84, P = 0.199). Restricting prednisolone usage to the former group would have reduced exposure by 87%. DISCUSSION: In a large cohort of patients with severe AH, serum K18 strongly correlated with histological severity, independently associated with 90-day mortality, and predicted response to prednisolone therapy. Quantification of serum K18 levels could assist in clinical decision-making.